Preparation method of high-specific-power manganese dioxide-carbon fluoride battery positive pole piece
By using graded ball milling dispersion and surfactant-assisted dispersion, combined with porous aluminum mesh and PTFE binder, the problems of uneven mixing and low loading of the positive electrode sheet of lithium primary batteries were solved, achieving battery performance with high specific power and high energy density.
Patent Information
- Application Number
- CN202511513552.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-22
- Publication Date
- 2026-01-23
AI Technical Summary
Existing lithium primary battery cathode sheets suffer from problems such as uneven mixing, low load capacity, and poor binder compatibility, resulting in insufficient energy density and high power performance.
By employing a graded ball milling dispersion and surfactant-assisted dispersion method, combined with a porous aluminum mesh current collector and an optimized PTFE binder, manganese dioxide and fluorinated carbon are uniformly mixed, and high-performance electrode sheets are formed through high-load coating and roll pressing.
A high-power-density and high-energy-density lithium primary battery cathode sheet has been developed, which is suitable for industrial mass production and improves the overall performance of the battery.
Smart Images

Figure CN121394288A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of preparation of positive electrode sheet of lithium primary battery, and particularly relates to a preparation method of manganese dioxide-carbon fluoride composite positive electrode sheet with high loading capacity and high uniformity, which is suitable for lithium primary batteries with high specific energy and high specific power. BACKGROUND
[0002] Lithium primary batteries have irreplaceable position in the fields of military communication, emergency power supply, aerospace, etc. due to their high energy density, long storage life, excellent low-temperature performance and other characteristics. The positive electrode material is the core that determines its performance. Among them, manganese dioxide (MnO2) has the advantages of good conductivity and stable discharge voltage, but the energy density is relatively low (theoretical specific capacity 308 mAh / g); carbon fluoride ((CF x ) has extremely high energy density (theoretical specific capacity 864 mAh / g), but poor intrinsic conductivity (electrical conductivity 10⁻¹ 4 S / cm), and serious polarization and low capacity retention rate during high-power discharge.
[0003] CN107316988B discloses a manganese dioxide chemically modified carbon fluoride material and its preparation method and application, which uses manganese dioxide modification and conductive polymer coated fluorinated graphene to improve the electronic conductivity of fluorinated graphene material itself, so as to improve the large-current discharge performance and capacity utilization rate of the positive electrode material; CN115714167B discloses a manganese dioxide chemically modified carbon fluoride material and its preparation method and application, which uses chemical synthesis to coat manganese dioxide on the surface of carbon fluoride, and the prepared electrode material has high voltage platform and high discharge specific capacity; CN107359316B discloses a lithium battery positive electrode material and its preparation method, which uses preparation of monodisperse fluorinated graphene solution and fluorinated graphene and manganese dioxide composite powder to form a uniform three-dimensional composite system, further improving the specific energy of the battery.
[0004] In the prior art, high-conductivity substances or manganese dioxide active substances are often introduced to improve the rate performance of the composite positive electrode, but due to the introduction of conductive substances without lithium intercalation capacity and the theoretical specific capacity of manganese dioxide being less than that of carbon fluoride, energy density loss is inevitable to some extent. In addition to the above problems, there are still two bottlenecks in improving the rate performance of carbon fluoride: (1) limited loading capacity of the positive electrode sheet: the flexibility of the traditional aluminum foil current collector is limited, and when coating the positive electrode slurry of the primary lithium battery, it is difficult to break through 500 g / m² of the double-sided area density of the loading capacity, and it is difficult to realize high-load coating while ensuring the rate performance, which is difficult to maintain the energy density of the battery; (2) insufficient compatibility of the binder: the adhesion strength of the commonly used binder PVDF is insufficient in the high-loading scenario, and the interface compatibility with carbon fluoride is poor, resulting in poor stability of the electrode sheet after long-term storage.
[0005] Therefore, it is of great significance to develop a preparation method of a composite positive electrode sheet with uniform mixing, high loading and high power adaptation for improving the comprehensive performance of lithium primary batteries. SUMMARY
[0006] The present application aims to overcome the defects of uneven mixing, low loading and poor adhesion of the prior art, and provide a preparation method of a manganese dioxide-carbon fluoride battery positive electrode sheet, which has good processing performance, high conductivity, power density and energy density, and excellent electrochemical performance. At the same time, the method is suitable for industrial mass production, making the manganese dioxide-carbon fluoride battery have great technical advancement in high-rate application scenarios. The specific technical solutions are as follows:
[0007] S1, manganese dioxide pretreatment: heat treating manganese dioxide in an oven at 350-400℃ for 14-18h to prepare the required manganese dioxide with a mixed crystal type of γ / β, wherein the component ratio of γ crystal type is 65%-85%.
[0008] S2, hierarchical ball milling dispersion: (1) preliminary dispersion: ball milling manganese dioxide and carbon fluoride (CFx, 0.5≤x≤0.8) at a speed of 200-300r / min for 1-2h, the particle size of manganese dioxide after ball milling is 1-15um, and the particle size of carbon fluoride after ball milling is 0.1-5um; (2) fine dispersion: mixing the ball-milled manganese dioxide, carbon fluoride and conductive agent (Super P Li, acetylene black , Super P Li, ketjen black one or several) in a mass ratio of (60%-80%):(10%-30%):(3%-10%), and then planetary dispersing at a speed of 2000-2500r / min for 1-2h to obtain a uniform composite material.
[0009] S3, slurry preparation: adding deionized water (30%-50% of the mass of the composite material) to the composite material, stirring for 3-5min at a stirring speed of 15-30r / min; then adding a fluorocarbon surfactant accounting for 0.5-2% of the total mass of deionized water and isopropyl alcohol accounting for 2-4% of the total mass of deionized water, stirring for 15-30min at a stirring speed of 15-30r / min; then adding a binder polytetrafluoroethylene emulsion accounting for 3%-6% of the mass of the composite material in S2, stirring for 1-3min at a stirring speed of 15-30r / min to form a manganese dioxide-carbon fluoride battery positive electrode slurry.
[0010] S4, coating and rolling: coating the prepared manganese dioxide-carbon fluoride battery positive electrode slurry on a current collector (the surface density is 80-180g / m2 The control of the positive electrode slurry loading amount is 460-580 g / m 2 ; and the positive electrode plate with a compaction ratio of 2.3-2.8 g / cm 3 is formed after rolling.
[0011] The beneficial effects of the present application are:
[0012] The present application is a preparation method of a high specific power manganese dioxide-carbon fluoride battery positive electrode plate, which comprises manganese dioxide pretreatment, hierarchical ball milling dispersion, slurry preparation, coating and rolling, and the core improvement point is:
[0013] Hierarchical ball milling + surfactant assisted dispersion: in view of the density difference of the two materials, through the hierarchical process of preliminary dispersion and fine dispersion, combined with the interface regulation effect (reducing surface tension and enhancing wettability) of the surfactant, uniform mixing at the microscale is realized.
[0014] Aluminum mesh current collector adapts to high loading: a porous aluminum mesh is used as the current collector, and the mesh structure can enhance the bonding force with the active material through mechanical anchoring, supporting a higher coating thickness; at the same time, the mesh provides a channel for ion transmission, relieving the ion diffusion resistance under high loading.
[0015] PTFE binder optimization: PTFE has excellent chemical stability and flexibility, and its fluorine-containing structure has better interface compatibility with carbon fluoride, which can ensure the integrity of the plate structure under high loading and reduce the shedding of active materials during discharge. BRIEF DESCRIPTION OF DRAWINGS
[0016] figure 1 The performance test curve of the battery prepared by the positive electrode plate of Example 1 is shown in the figure;
[0017] figure 2 The performance test curve of the battery prepared by the positive electrode plate of the comparative example is shown in the figure; DETAILED DESCRIPTION
[0018] In order to further understand the content, characteristics and effects of the present application, the present application will be further described in conjunction with specific embodiments. The specific implementation is as follows:
[0019] S1, manganese dioxide pretreatment: heat the manganese dioxide in an oven at 350-400℃ for 14-18h to prepare the required manganese dioxide crystal type as a mixture of γ / β crystal type.
[0020] S2, hierarchical ball-milling dispersion: (1) preliminary dispersion: the manganese dioxide and carbon fluoride (CFx, 0.5≤x≤0.8) are ball-milled respectively at a speed of 200-300 r / min for 1-2 h, the particle size of the ball-milled manganese dioxide is 1-15 um, and the particle size of the ball-milled carbon fluoride is 0.1-5 um; (2) fine dispersion: the ball-milled manganese dioxide, carbon fluoride and conductive agent (one or several kinds of mixture) are mixed in a mass ratio of (60%-80%):(10%-30%):(3%-10%), and then the mixture is dispersed at a speed of 2000-2500 r / min for 1-2 h by a planetary mill to obtain a uniform composite material. acetylene black , Super P Li, ketjen black one or several kinds of mixture) are mixed in a mass ratio of (60%-80%):(10%-30%):(3%-10%), and then the mixture is dispersed at a speed of 2000-2500 r / min for 1-2 h by a planetary mill to obtain a uniform composite material.
[0021] S3, slurry preparation: deionized water (30%-50% of the mass of the composite material) is added to the composite material, and stirred for 3-5 min at a stirring speed of 15-30 r / min; then 0.5-2% of a fluorocarbon surfactant and 2-4% of isopropyl alcohol based on the total mass of the deionized water are added respectively, and stirred for 15-30 min at a stirring speed of 15-30 r / min; then a binder polytetrafluoroethylene emulsion is added and stirred, wherein the mass ratio of the binder polytetrafluoroethylene emulsion to the composite material in S2 is 3%-6%, and the stirring is performed for 1-3 min at a stirring speed of 15-30 r / min, to form a manganese dioxide-carbon fluoride battery positive electrode slurry.
[0022] S4, coating and rolling: the prepared manganese dioxide-carbon fluoride battery positive electrode slurry is coated on a current collector (the areal density is 80-180 g / m 2 ) by an extrusion or roller coating method, the loading amount of the positive electrode slurry is controlled, and the double-sided areal density is 460-580 g / m 2 ; after vacuum drying at 150-180 ℃ for 2 h, a positive electrode sheet with a compaction ratio of 2.3-2.8 g / cm 3 is formed after rolling.
[0023] Example
[0024] S1, manganese dioxide pretreatment: the manganese dioxide is heat-treated in an oven at 390 ℃ for 17 h to prepare the desired γ / β mixed crystal type of manganese dioxide.
[0025] S2, classification ball mill dispersion: (1) preliminary dispersion: the manganese dioxide, carbon fluoride (CFx, x=0.8) is ball milled respectively under the speed of 200 r / min for 2 h, the particle size of manganese dioxide after ball milling is 1-15 um, the particle size of carbon fluoride after ball milling is 0.1-5 um; (2) fine dispersion: the ball milled manganese dioxide, carbon fluoride and conductive agent Super P Li are mixed according to the mass ratio of 80%:15%:5% and then dispersed at the speed of 2500 r / min for 2 h by planetary, to obtain a uniform composite material.
[0026] S3, slurry preparation: deionized water (35% of the mass of the composite material) is added to the composite material, stirring for 5 min, stirring speed 30 r / min; then 2% of the total mass of the fluorocarbon surfactant and 2-4% of the total mass of the deionized water isopropanol is added, stirring for 15 min, stirring speed 15 r / min; then the binder polytetrafluoroethylene emulsion is added for stirring and mixing, wherein the binder polytetrafluoroethylene emulsion accounts for 3% of the mass ratio of the composite material in S2, stirring for 3 min, stirring speed 30 r / min, to form a manganese dioxide-carbon fluoride battery positive electrode slurry.
[0027] S4, coating and rolling: the prepared manganese dioxide-carbon fluoride battery positive electrode slurry is coated on an aluminum mesh (surface density 120-180 g / m 2 ) of certain surface density and porosity by extrusion or roller coating, the positive electrode slurry loading is controlled, and the double-sided surface density is 560 g / m 2 ; vacuum drying at 180℃ for 2 h, and after rolling, a positive electrode sheet with a compaction ratio of 2.5 g / cm 3 is formed.
[0028] Comparative example (traditional manganese dioxide-carbon fluoride battery positive electrode sheet preparation process)
[0029] S1, manganese dioxide pretreatment: the manganese dioxide is heat treated in an oven at 390℃ for 17 h, to prepare the required manganese dioxide with γ / β mixed crystal type.
[0030] S2, active material dispersion: the pretreated manganese dioxide, carbon fluoride and conductive agent Super P Li are mixed according to the mass ratio of 80%:15%:5% and then dispersed at the speed of 2500 r / min for 2 h by planetary, to obtain a uniform composite material.
[0031] S3, slurry preparation: PVDF (5% of the mass of the composite material) is dissolved in NMP solvent, stirring for 2 h, dispersion speed 500 r / min to form PVDF glue (solid content 8%); the composite material in (1) is added to the PVDF glue, stirring for 2 h, dispersion speed 500 r / min, to form a manganese dioxide-carbon fluoride battery positive electrode slurry.
[0032] S4, the prepared manganese dioxide-carbon fluoride battery positive electrode slurry is coated on a certain surface density aluminum foil (surface density is 45 g / m 2 ) by extrusion or roller coating method, the positive electrode slurry loading is controlled, and the maximum loading of the aluminum foil reaches only 480 g / m 2 ; vacuum drying at 180℃ for 2h, and forming a positive electrode sheet with a compaction ratio of 2.1 g / cm 3 after rolling.
[0033] The examples and comparative examples are prepared by using the existing conventional soft package lithium metal battery preparation process, and the only variable is the positive electrode sheet preparation method. figure 1 The battery performance test curve prepared by the positive electrode sheet of the examples and comparative examples is shown, and the energy density of the examples is improved by 33.2% compared with the comparative examples at 1C (about 14A) high rate output.
[0034] Table 1
[0035] case battery weight discharge regime delivered energy energy density example 82g 14a constant current to 1.5v 37.2wh 453wh / kg comparative example 81g 14a constant current to 1.5v 27.6wh 340wh / kg
[0036] The present application is not limited to the above examples, any modification, equivalent replacement, improvement, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing a high specific power manganese dioxide-carbon fluoride battery positive electrode sheet, comprising the following steps: Step one, pretreatment of manganese dioxide: heat-treating manganese dioxide in an oven at 350-400℃ for 14-18h to prepare the desired manganese dioxide crystal form; Step two, hierarchical ball-milling dispersion: (1) preliminary dispersion: independently ball-milling manganese dioxide and carbon fluoride at a speed of 200-300r / min for 1-2h; (2) fine dispersion: mixing the ball-milled manganese dioxide and carbon fluoride with a conductive agent at a mass ratio of 60%-80%:10%-30%:3%-10%, and then dispersing at a speed of 2000-2500r / min for 1-2h to obtain a uniform composite material; Step three, slurry preparation adding deionized water to the composite material at a mass ratio of 30%-50% of the composite material, stirring for 3-5min at a stirring speed of 15-30r / min; then adding a surfactant at a mass ratio of 0.5-2% of the total mass of the deionized water and isopropyl alcohol at a mass ratio of 2-4% of the total mass of the deionized water, stirring for 15-30min at a stirring speed of 15-30r / min; then adding a binder at a mass ratio of 3%-6% of the composite material in step two, stirring for 1-3min at a stirring speed of 15-30r / min to form a manganese dioxide-carbon fluoride battery positive electrode slurry; Step four, coating and rolling coating the prepared manganese dioxide-carbon fluoride battery positive electrode slurry on an aluminum mesh current collector with a certain surface density by extrusion or roller coating, controlling the loading amount of the positive electrode slurry, and then forming a high-loading manganese dioxide-carbon fluoride battery positive electrode sheet with a certain compactness and surface density after vacuum drying and rolling.
2. The method for preparing a positive electrode sheet for a high specific power Mn02-CFx battery as claimed in claim 1, wherein the step of mixing the Mn02 and CFx is performed by mixing the Mn02 and CFx in a weight ratio of 1:1 to 1:
3. Step one, preparing the desired manganese dioxide crystal form as a γ / β mixed crystal form of manganese dioxide, wherein the γ crystal form component ratio is 65%-85%.
3. The method for preparing a positive electrode sheet for a high specific power Mn02-CFx battery as claimed in claim 1, wherein the step of mixing the Mn02 and CFx is performed by using a ball mill or a jet mill. 5 The particle size of the ball-milled manganese dioxide is 1-15um, the carbon fluoride is a fluorocarbon compound CFx, 0.5≤x≤0.8, and the particle size after ball-milling is 0.1-5um.
4. The method of claim 1, wherein the manganese dioxide-carbon monofluoride battery positive electrode plate is prepared by the steps of: a) mixing manganese dioxide, carbon monofluoride, and a binder to form a mixture; b) coating the mixture on a substrate to form a positive electrode plate; and c) drying the positive electrode plate. The dispersion device is a planetary type.
5. The method for preparing a high specific power manganese dioxide-carbon fluoride battery positive electrode sheet as described in claim 1, characterized in that: The electrically conductive agent is acetylene black , Super P Li, ketjen black one or several mixtures thereof.
6. The method for preparing a high specific power manganese dioxide-carbon fluoride battery positive electrode sheet as described in claim 1, characterized in that: The surfactant is a fluorocarbon surfactant.
7. The method for preparing a high specific power manganese dioxide-carbon fluoride battery positive electrode sheet as described in claim 1, characterized in that: The binder is a polytetrafluoroethylene emulsion.
8. The method for preparing a high specific power manganese dioxide-carbon fluoride battery positive electrode sheet as described in claim 1, characterized in that: The current collector is aluminum plate net, aluminum plate cable-stayed current collecting net, aluminum foil net, micro-porous aluminum plate foil cable-stayed net, and the area density is 80-180 g / m 2 .
9. The method for preparing a high specific power manganese dioxide-carbon fluoride battery positive electrode sheet as described in claim 1, characterized in that: The positive electrode sheet of the manganese dioxide-carbon fluoride battery has a double-sided area density of 460-580 g / m after coating 2 , and a compactness of 2.3-2.8 g / cm after rolling after vacuum drying at 150-180℃ for 1-2 h 3 .
Citation Information
Patent Citations
A composite positive electrode material for lithium carbon fluoride battery and its preparation method
CN107316988B
A lithium battery cathode material and its preparation method
CN107359316B
A manganese dioxide chemically modified carbon fluoride material and its preparation method and application
CN115714167B
Cited By
Oil system homogenizing method of power type lithium primary battery positive electrode slurry
CN122136275A